2017
DOI: 10.3389/fphys.2017.00555
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Analysis of Oxygen Saturation Variability in Healthy Individuals: Entropy of Pulse Oximetry Signals Carries Information about Mean Oxygen Saturation

Abstract: Pulse oximetry is routinely used for monitoring patients' oxygen saturation levels with little regard to the variability of this physiological variable. There are few published studies on oxygen saturation variability (OSV), with none describing the variability and its pattern in a healthy adult population. The aim of this study was to characterize the pattern of OSV using several parameters; the regularity (sample entropy analysis), the self-similarity [detrended fluctuation analysis (DFA)] and the complexity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 42 publications
3
65
1
1
Order By: Relevance
“…Costa et al extended the concept of entropy by incorporating multiple scales calculation of SampEn in a time-series (9). Such multiscale entropy method has been used to measure the complexity of different physiological time-series such as HRV and oxygen saturation variability (21). In present study, HRC was defined as the summation of entropies of scales from 1 to 20 as described (16).…”
Section: Kurtosismentioning
confidence: 99%
“…Costa et al extended the concept of entropy by incorporating multiple scales calculation of SampEn in a time-series (9). Such multiscale entropy method has been used to measure the complexity of different physiological time-series such as HRV and oxygen saturation variability (21). In present study, HRC was defined as the summation of entropies of scales from 1 to 20 as described (16).…”
Section: Kurtosismentioning
confidence: 99%
“…Therefore, in this work, we used Multiscale Entropy (MSE) for the feature extraction method of SpO2 and PR signals to analyze the feature vectors of three human emotions. This method is an extension of sample entropy and has been used by some researchers to describe complexity in a time series [9][10] [11][12] [13]. The purpose of complexity in this context can be defined as "a meaningful structural richness" which incorporates correlation over several temporal scales [9].…”
Section: Introductionmentioning
confidence: 99%
“…Day-to-day SpO 2 fluctuations have not yet received a lot of attention in scientific literature and night-to-night fluctuations have not yet been studied over more than two nights in patients with COPD. Some studies examined intraday fluctuations, however, these studies only examined short-term SpO 2 fluctuations (ie, measurements of one hour or less) in healthy individuals [29] or infants [26-28]. Our results showed that significant SpO 2 fluctuations occurred between and within multiple days and nights for the included patients.…”
Section: Discussionmentioning
confidence: 69%
“…One hour of daytime measurements was considered sufficient to examine whether significant fluctuations occurred in SpO 2 values during the day. Previous studies examining intraday fluctuations only examined measurements of one hour or less [26-29]. No days or nights had to be excluded due to lacking SenseWear Armband measurements.…”
Section: Methodsmentioning
confidence: 99%